Successful stenting of a pulmonary arterial stenosis after a single lung transplant. Issue 9 (September 1995) - Ferretti, G; Boutelant, M; Thony, F; Carpentier, F; Pison, C; Guignier, M
Abstract : A 44 year old patient with end stage idiopathic pulmonary fibrosis underwent single left lung transplantation. A perfusion lung scan performed 13 days after transplantation revealed deficient perfusion in the transplanted lung. Pulmonary angiography showed severe pulmonary artery anastomotic stenosis. Percutaneous insertion of a balloon expandable stent improved both pulmonary perfusion and respiratory function.